Work Motivation and Job Satisfaction of Local Government Employees in Matalam, Cotabato Philippines: A Basis for Intervention Program - Nitafan, Rowell P.; Camay, Janette C. (International Journal of Humanities and Education Development (IJHED), 2020)
The study was a descriptive-correlational research. It primarily aimed to determine the significant relationship between the work motivation and job satisfaction of regular employees of the municipal local government of Matalam, Cotabato, Philippines. The study found out that regular employees have moderate level of work motivation with a high level of need of affiliation and achievement while moderate level of need of power. Moreover, the study determined that the regular employees have a high level of job satisfaction at work with high level of satisfaction on co-workers’ support and work conditions while moderate level of satisfaction on benefits and managerial support. Moreover, the study also proposed an intervention program that the Heads, Supervisors and Human Resource Management Development Office may use as a keystone in addressing problems on work motivation explored in the study such as issues on wanting to be liked by others, finding themselves talking to those around them about non-work matters, inability to solve the problems that arise in work and issues on being in charge. The intervention program also had recommendations to address problems on job satisfaction of the regular employees such as issues on their current salary on meeting their qualification, colleagues on giving them opportunities to contribute ideas from various perspectives, contentment on working under the supervision, continuous feedback of the supervisor to help them achieve the goals, and meeting career objectives through the current jobs. Lastly, the research determined a positive yet low relationship between the work motivation and job satisfaction of the regular employees. Nevertheless, the study concluded that the correlation that was found between the variables was insignificant and due to probability. Also, no dimension of work motivation was found to be statistically significantly associated with any of the dimensions of job burnout.